Efektifitas Instagram dalam Pembelajaran Bahasa Inggris di Program Studi Teknik Informatika - Bayu Ardiansyah (Universitas Indraprasta PGRI Jakarta, 2023)
One of the main subjects that students must study in their chosen field is English. English for specific purposes (ESP) is the ability to speak English suitable for a specific purpose. Writing is one of the skills whose performance is less than optimal for students in the Informatics Engineering study program. In an era where digital technology has become an important consumption and need for society, social media has become one of the things that young people really like. Therefore, this research uses social media, especially Instagram, as a teaching tool and can motivate students to learn English. Data collection techniques include written results, pre and post tests, as well as observation and documentation. To determine the effectiveness of Instagram social media as a learning tool, it will be evaluated based on the results of a student questionnaire. The sample for this research was 30 IT students. The steps in the data collection process in this research include, for example. (1) observation of the research object, (2) socialization stage to students about learning through social media, especially Instagram, (3), implementation of this research, in this phase students receive material at the beginning where they not only get the material, but also must look for other supporting materials and discuss and receive suggestions and comments from lecturers and friends, (4) The final stage is the introduction stage of using Instagram as a means of discussion and debate. as a place to publish student work.